Investigating the Outcomes of Adolescent Treatment for Humerus Fractures Using Elastic Titanium Nails - Pouria Tabrizian (Archives of Advances in Biosciences)
Introduction: Intramedullary interlocking nails are commonly used for humerus fracture fixation in children and adolescents. Although effective, this method can disrupt medullary blood flow and pose biomechanical challenges. Titanium elastic nails (TEN) offer a less invasive alternative with fewer complications, yet limited studies have compared TEN with other fixation methods in this age group. This study aimed to evaluate the outcomes of TEN for humerus fractures in pediatric patients. Materials and Methods: In this cross-sectional study, pediatric patients who underwent humerus fracture fixation with TEN at Shafa Hospital (2019–2020) were assessed. Functional outcomes were evaluated using the Disability of Arm, Shoulder, and Hand (DASH) Score; pain was measured by the Visual Analog Scale (VAS), and elbow range of motion was measured with a goniometer. Complications, including infection and nerve injury, were recorded. Results: Among the 23 patients treated with TEN, the mean age was 8.5 years. Postoperative complications occurred in 17.4% of cases, including hematoma, nail tip protrusion, and superficial infection. There were no significant differences in range of motion between male and female patients. Conclusion: Titanium elastic nails provide a safe and effective option for humerus fracture fixation in children, offering favorable outcomes with minimal complications.